Investigation into psychological contract in ethically disciplined group: a case study of academics in Chinese higher education - Fu, Yao; Xu, Yuan (Frontiers in Psychology, 2023)
Ethical values and beliefs are increasingly realized as important factors in the operation of psychological contract for their potential role in determining individuals' attitudes toward employment relationships by valuing mutual exchange. However, to incorporate ethical terms into psychological contract analysis is challenging because they are often confused with relational contract, and ethics of professions can be difficult to summarize and interpret. This study has demonstrated how psychological contract operates within academics in Chinese higher education, an occupational group that is typically considered ethically disciplined and culturally bonded to their identity. Here, we designed a questionnaire survey focusing on transactional/relational psychological contract, ethical framework, and job performance, and statistically analyzed the responses to this survey from 230 Chinese higher education academics. It finds that the sample population perceived psychology contact with a relatively low contribution from monetary terms, while a strong correlation was observed between ethics and relational terms. In addition, the influence of emotional and ethical terms on job performance was clearly differentiated in statistics. From analyzing through a mediation model, it suggested an intermediated role of ethics between psychological contract and job performance. Findings in this study have demonstrated that ethically disciplined groups exhibit unique features in both their perceptions of psychological contract and their correlation with ethics and job performance, which is anomalous in other occupations. This study provides a protocol demonstrating the role of ethical framework in the operation of psychological contract, particularly within occupational groups bonded strongly to their identity/profession and constrained by ethics imposed by the society.